The Dark Triads Influence upon Academic Breach Action throughout Online Learning - Satsya Yoga Baswara; Edy Suryanto; Radinta Maharani; Jarot Tri Bowo Santoso (LP3M Universitas Putra Bangsa, 2022)
Covid – 19 has given rise to learning options with the concept of distance education through online learning applications such as zoom, google meet, MS Teams, etc. and even the use of learning applications developed by higher education itself. This was done to avoid crowds as requested by the government referring to the WHO Health protocol. This is actually a very good boost for the world of Indonesian education. However, it creates another problem, which are quite disturbing and have the potential to damage the quality of the output of Indonesia education itself. The problem is cheating in online learning. This becomes very important, especially in the context of higher education. Why, because in higher education, students have become an adult learner so they are quite free from parental supervision at home, unlike the concept of online schools in elementary, junior high and high school. Considering the importance of this academic violation, to get a more comprehensive understanding of how and why cheating is done in the context of online lectures in universities by using variables related psychological traits that in line of phycological called as the dark triads (psychopathy, narcissism, and Machiavellianism) on student attitudes in online lectures.